Healthcare for Transgender Youth: Still Inadequate...Still at Risk. Issue 5 (September 2017) - Beal, Judy A.
Abstract : With accurate and up-to-date knowledge, pediatric nurses can take the lead in advocating for evidence-based culturally competent care for transgender youth in all pediatric settings. Per our pediatric nursing expert, Dr. Beal, as nurses, we are in a unique role as the most trusted of healthcare professionals to be able to support these very vulnerable teens and their caregivers.